2023
DOI: 10.1002/ppul.26646
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 lockdown measures on symptoms control in children with asthma: A systematic review and meta‐analysis of observational cohort studies

Panayiotis Kouis,
Marios Lemonaris,
Eleana Xenophontos
et al.

Abstract: ObjectivesReported reductions in emergency department visits and hospitalizations for asthma in previous studies have suggested a beneficial effect of the coronavirus disease of 2019 (COVID‐19) lockdown measures on asthma morbidity. Nevertheless, studies relying on administrative data may overestimate the true impact of lockdowns due to changes in health‐seeking behavior and reduced availability of pediatric asthma services during the pandemic. In this study, we systematically reviewed the literature and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
(214 reference statements)
1
0
0
Order By: Relevance
“…Moreover, the higher the RSV infection severity, the stronger the link. Our parent‐reported data on the link between RSV infection and wheezing is in line with previously published data from the structured research context 19–23 . A retrospective study on >68,000 children reported a higher risk of wheezing/asthma in RSV hospitalized infants compared to controls 13 .…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the higher the RSV infection severity, the stronger the link. Our parent‐reported data on the link between RSV infection and wheezing is in line with previously published data from the structured research context 19–23 . A retrospective study on >68,000 children reported a higher risk of wheezing/asthma in RSV hospitalized infants compared to controls 13 .…”
Section: Discussionsupporting
confidence: 89%